Encountering premature ovulation during controlled ovarian hyperstimulation in IVF/ICSI cycles - Frank Shao-Ying Wu; Robert Kuo-Kuang Lee; Yuh-Ming Hwu (Elsevier, 2012)
Objective: To report successful pregnancy outcomes in three cases of documented premature ovulation in intracytoplasmic sperm injection (ICSI) cycles. Case Report: Three cases of premature ovulation were noted during the oocyte retrieval procedures in in vitro fertilization (IVF)/ICSI cycles with gonadotropin-releasing hormone antagonist protocol. Immature oocytes were aspirated from the remaining small and medium-sized follicles with in vitro maturation performed in two cases. All three cases achieved successful pregnancy with documented live birth after ICSI. Conclusion: This is the first ever report of successful pregnancy outcome after documented premature ovulation. Fertilizable oocytes and successful pregnancies can still be obtained from the remaining small and medium-sized follicles after premature ovulation and used for ICSI.